Puncture and discission with a needle: A new method for laparoscopic common bile duct exploration. Issue 38 (18th September 2020) - Xie, Zhiqin; Li, Hongxia; Sun, Yongkang; Chen, Xun; Tang, Caixi
Abstract : Abstract: This study aimed to describe a novel puncture and discission with a needle (PDN) method facilitating laparoscopic common bile duct exploration (LCBDE). The clinical data of 81 patients with cholelithiasis or choledocholithiasis who underwent LCBDE with PDN between January, 2017 and December, 2017 were retrospectively analyzed. Time for puncture and discission of the bile duct, blood loss, postoperative complications (such as bile leakage, common bile duct [CBD] strictures, and recurrence of choledocholithiasis), and postoperative hospital stay were recorded to evaluate the safety of the method. PDN was performed in all 81 patients with a 100% surgical success rate. Surgery went smoothly. Neither mortality nor complications associated with PDN (portal vein injury or biliary leakage) were observed. The mean time for puncture and discission of the CBD was 2.4 minutes and the maximum blood loss was 100 mL. CBD strictures or recurrence of choledocholithiasis were not noted after 12 to 24 months of follow-up. LCBDE with PDN is a novel method and has the advantages of reliability, convenience, and efficiency without additional costs or complications.